(untitled) (Indonesian Journal of Pharmaceutical and Clinical Research, 2021)
Data showed that 235 million people suffer from asthma with death rate more than 80% in developing countries. The pharmacist’s role in managing asthma is to overcome drug-related problems that arise, provide information and counseling, motivate patients to adhere the treatment and assist in Medication Record. This study aims to determine the effect of the application of pharmaceutical care on drug therapy problems, adherence, therapeutic outcomes and quality of life in asthma patients. Data were carried out based on observation, interviews, and through filling questionnaires by asthma patients who redeem prescriptions at Apotek Dety Jl. Kapten Muslim No. 45A Medan from July to November 2020 who met the inclusion criteria. Number of DRP incidents obtained according to PCNE V9.0. Data were analyzed statistically used the Friedman and Wilxocon test. The result showed that There was a significant decrease in the problem group after the intervention was carried out by 93.3%. Based on the results of the study it can be concluded that the application of pharmaceutical care in asthma patients has a significant effect on reduced drug therapy.